2006
DOI: 10.1007/s10194-006-0283-5
|View full text |Cite
|
Sign up to set email alerts
|

Great occipital nerve blockade for cluster headache in the emergency department: case report

Abstract: IntroductionCluster headache (CH) is characterised by attacks of severe unilateral pain in the orbital, supraorbital and/or temporal areas, lasting from 15 up to 180 min, recurring up to 8 times daily and accompanied by ipsilateral autonomic symptoms. In the episodic form, headache attacks usually occur in bouts (cluster periods) lasting from one week to 1 year, separated by pain-free periods of at least 1 month. In the chronic form these pain-free periods are absent or last less than a month [1].Although effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…28 Occipital neuralgia may present with other symptoms, including nausea, tinnitus, dizziness, and visual disturbance, symptoms that overlap with migraine and cluster headache. 29,30,31 Given the lack of diagnostic consensus, it becomes difficult to interpret the literature with regard to efficacy of various treatments. It seems increasingly apparent that these disorders exist along a continuum of headache pain that is likely multifactorial and interrelated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…28 Occipital neuralgia may present with other symptoms, including nausea, tinnitus, dizziness, and visual disturbance, symptoms that overlap with migraine and cluster headache. 29,30,31 Given the lack of diagnostic consensus, it becomes difficult to interpret the literature with regard to efficacy of various treatments. It seems increasingly apparent that these disorders exist along a continuum of headache pain that is likely multifactorial and interrelated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found GONB to be effective in migraine [9][10][11][12], cluster headache [4,13], posttraumatic headache [14], and in two cases of hemiplegic migraine, or attacks of migraine with unilateral motor symptoms [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Among these are interruption or decompression of the trigeminal tract, nerve, ganglion, roots, and nerves [24][25][26][27][28][29][30][31], interruption of the sympathetic pathways to the face [32], chemical or surgical interruption of the facial parasympathetic pathways to the face, including the nervus intermedius [27,33], greater super- fi cial petrosal nerve, and SPG [34][35][36][37][38]. Finally, stimulation, block and interruption of the vagus nerve [39], occipital nerve [40,41] and most recently deep brain stimulation within the posterior hypothalamus have brought some pain relief [42,43].…”
Section: Discussionmentioning
confidence: 99%